CRITICAL ANALYSIS OF PHARMACIST-LED SMOKING CESSATION INTERVENTIONS. - Saeed Mohamad Rashed Al Rashadi, Mohammed Debshan M Alahmari, Ali Hassan Ali Sulaiman, Abdulrahman Awadh Alwadai, Abdullatif Saad Alqahtani, Waleed Ibrahim Mohammed, Bassam Aowdh Alwadai, Saeed Abdulrahman Ali Hafez, Abdullah Obeid Salem Al Marwani (Chelonian Research Foundation, 2022)
This paper critically looks into the smoking cessation interventions led by pharmacists; it considers the effectiveness of such interventions, the accompanying challenges, and the consequences of their implementation. The strategy begins with an outlined literature review to focus on the pharmacist's role in smoking cessation, the different intervention measures taken, and the effects on smoking-quitting success rates and patients' health outcomes. The way subjects may be recruited, the results and the data from these studies are all presented, where they appear as graphs, tables, and figures, among other visual aids, to deepen comprehension of key points. This session examines the pharmacists' roles and responsibilities in smoking cessation programs, including strengths and challenges. Also, it introduces areas that research ought to cover and provides recommendations for better integration of pharmacists in the smoking cessation process. Keywords: Pharmacist, smoking cessation, interventions, effectiveness, patient outcomes